Water, its Owners and the Mapuche Spirit - Antona Bustos, Jesus (2026)
For the Mapuche, good water is linked to the balance between the different elements and beings of nature, which is why water and ko are different entities. Water is a constituent part of Mapuche identity and the mirror in which the purity of their spirit is reflected. Therefore, ko is synonymous with pure and free water, which runs through the veins of the territory, interacting, mixing and transmuting with the souls and species of the ethnic space. It is also the vital energy that is in symbiosis with native species and the fluid that certain entities (geh) are responsible for promoting and protecting in order to preserve life. This work highlights that water (ko), in addition to being a vital resource and an essential fluid, is fundamentally a spiritual entity whose agency manifests itself within a network of fluid relationships that allow water to be produced, maintained and transformed within the complex Mapuche geography, which is eminently moral rather than biophysical.